Hip Bop: The imaginary collaborations of Miles Davis - Maloney, Liam (Jazz Research Journal, 2022)
This article explores Afrofuturist countermemory and alternative history, and the potential of these concepts to be applied to the legacy of Miles Davis’s final fusion concept. Through artistic practice and investigations into the role of such practice in musicological research, Kodwo Eshun’s ‘sonic fictions’ are leveraged as a lens to reclaim Davis’s experiments in jazz-hip hop fusion. Afrofuturism and its relation to speculative modalities is discussed, particularly in terms of its capacity for cultural recovery and historical disruption with a focus on recorded music via sonic fictions and their attendant considerations. The practice-led research brings the ‘conceptual collaboration’ paradigm of Amerigo Gazaway to bear on Davis’s work; four guiding principles in Gazaway’s concept are identified and discussed. The culmination of this research, an original album titled Hip Bop, imagines an alternative future for Miles Davis post-1992 that continues and expands the jazz-hip hop fusion of his final album. This new album is then discussed with reference to sonic fiction, and its relationship to authenticity and techno-political expression is questioned.